STABILITY INDICATING HPTLC METHOD FOR SOFOSBUVIR AND VELPATASVIR IN COMBINATION (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The discovery of new direct-acting antiviral drugs gave rise to a leap forward in the treatment of hepatitis C viral infections. For the first time since 1998, the Food and Drug Administration (FDA) approved interferon-free oral treatment paradigms. Among the new treatment regimens, the combinations of Sofosbuvir and Velpatasvir became ideal treatment regimens for being potent, highly tolerated and used once daily. Hence an accurate, precise, selective and sensitive stability indicating method for simultaneous estimation of Sofosbuvir and Velpatasvir by High-Performance Thin Layer Chromatography has been developed and validated. Chromatographic separation was achieved on TLC plates coated with silica gel 60 F254 as stationary phase. Ethyl acetate: iso-propyl alcohol (9:1 v/v) was used as mobile phase.Densitometric scanning was carried out at 260 and 302 nm for Sofosbuvir and Velpatasvir, respectively. The method was successfully validated as per the ICH Guideline. The linear concentration range was100- 2000 ng/band (r2= 0.991) and 100-500 ng/band (r2 = 0.991) for SOF (Sofosbuvir) and VEL (Velpatasvir) respectively. The LOD were 25.16 ng/band and 9.96 ng/band for SOF and VEL, LOQ were 76.25 ng/band and 30.19 ng/band for SOF and VEL.The method could be applied to the quality control and routine analysis of Sofosbuvir and Velpatasvir in their pure forms and pharmaceutical formulations.